Hospital Nurses’ Risk of Injury: A Mixed Methods Study in Indonesia - Sri Yulia; Achir Yani S.Hamid; Hanny Handiyani; Ede Surya Darmawan (Pacific Rim International Journal of Nursing Research, 2023)
Various risks of injury become the background of incidents and health and safety problems for nurses globally, impacting a nurse’s right to a safe work environment. No studies have examined the relationship between individual conditions and various aspects of the nurse’s risk of injury. This study explored nurses’ risk of injury in hospitals and the relationship between the individual characteristics of nurses with the surveillance, screening and injury prevention activities undertaken in hospitals. This mixed methods study using an exploratory sequential design was conducted in Indonesia involving 176 registered nurses from 17 urban hospitals for the quantitative phase and 21 registered nurses from five hospitals for the qualitative phase. The quantitative data shows that more than half stated they were not good at occupational health and safety surveillance or screening or efforts to reduce occupational health and safety risks. The surveillance, screening, and injury prevention activities of the nurses in the hospitals were not found to be influenced by their age, working experience, marital status, gender, education level, and employment status. The qualitative data analysis revealed four main themes: (1) Causes of the nurses’ risk of injury, (2) Preventing injuries, (3) Resilience, and (4) Acting to prevent risk of injury. The effective methods to prevent the risk of injury included optimizing nurses’ roles, improving the work environment, and making organizational programs on health and safety. Nurses are exposed to multiple risks of injury, and their monitoring, screening, and injury prevention activities are influenced by factors other than the individual.